2016
DOI: 10.3390/hydrology3040034
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Climate Change on Urban Stormwater Infrastructures in the Las Vegas Valley

Abstract: Abstract:The intensification of the hydrological cycle due to climate change entails more frequent and intense rainfall. As a result, urban water systems will be disproportionately affected by the climate change, especially in such urban areas as Las Vegas, which concentrates its population, infrastructure, and economic activity. Proper design and management of stormwater facilities are needed to attenuate the severe effects of extreme rainfall events. The North American Regional Climate Change Assessment Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…This situation could make lakes and reservoirs more vulnerable to eutrophication [1][2][3]. In recent years, climate change and its impacts on the quantitative and qualitative aspects of water have been the focus of several studies [4][5][6]. Various climate models and scenarios were used to investigate possible climate change impacts on hydrological variables [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This situation could make lakes and reservoirs more vulnerable to eutrophication [1][2][3]. In recent years, climate change and its impacts on the quantitative and qualitative aspects of water have been the focus of several studies [4][5][6]. Various climate models and scenarios were used to investigate possible climate change impacts on hydrological variables [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the river flood management, the Ellicott City needs an improvement in its existing stormwater system to handle the severe storms which devastate the city frequently. A method followed by Thakali et al (2016) that considers the impact of changing climate on the stormwater infrastructure might be useful in evaluating and designing the flood management infrastructure. Thakali et al, (2016) conducted a study over the stormwater system of Las Vegas area and found it to be inadequate to handle the catchment flow in the future climate.…”
Section: Inundation Mapping In Arcgis Using Hec-georas Extensionmentioning
confidence: 99%
“…ECB 2016-25 provisioned qualitative analysis of historical climate trends, as well as assessment of future projections. As the impacts of climate change to the hydrologic characteristics of a basin are realized, streamflow forecasting can become difficult for hydrologists and climatologists as past hydrologic conditions are no longer representative of future conditions (Pathak et al 2016;Thakali et al 2016;Tamaddun et al 2017). It is important to understand the relationship between climate variability and the hydrologic response of a basin such that sustainable and efficient management of water-related systems can be implemented (Middelkoop et al 2001;Pahl-Wostl 2007;Kundzewicz et al 2008).…”
Section: Introductionmentioning
confidence: 99%